Nutritional status of iron and vitamin D in postpartum women in northern Taiwan - Li, Sing-Chung; Chen, Yi-Ling; Chen, Chiao-Ming; Tsai, Li-Yi; Mu, Shu-Chi (Frontiers in Nutrition, 2026)
BackgroundPostpartum women are at increased risk of iron and vitamin D deficiencies due to physiological demands, blood loss during delivery, and limited sun exposure during the confinement period. The aimed of this study was to assess the iron and vitamin D nutritional status of women at six weeks postpartum in northern Taiwan and to examine its associations with dietary intake and nutritional supplement use.MethodsThis cross-sectional study included 120 women at six weeks postpartum in northern Taiwan. Dietary intake was assessed using 24-h dietary recall, and supplement use was recorded. Hematological and biochemical parameters, including hemoglobin, ferritin, and serum 25(OH)D3, were measured.ResultsThe prevalence of iron deficiency and iron deficiency anemia was 5.0% and 6.7%, respectively, while 75% of women exhibited vitamin D insufficiency or deficiency. Supplement users had a significantly lower prevalence of iron deficiency and vitamin D deficiency compared with non-users.ConclusionOur findings suggest that dietary intake alone is insufficient to meet postpartum micronutrient requirements and that supplementation plays a critical role in maintaining adequate nutritional status. These results highlight the need for targeted nutritional strategies and updated dietary recommendations to support maternal recovery and health after childbirth.